The Effect of Childhood Nutritional Status Changes with Pre-Diabetes And Diabetes Risk among Adolescents: A Retrospective Cohort Study - Komang Dwi Pradnyani Laksmi; Ikeu Tanziha; Yayuk Farida Baliwati (Green Publisher Indonesia, 2024)
The first 1000 days of life and before the age of five years is a critical period of nutritional opportunity and vulnerabilitya. Only few have studies that trace individuals from childhood to adolescence examined the influence of childhood undernutrition on diabetes risk. This research was a retrospective cohort study using secondary data from IFLS (Indonesian Family Life Survey) involving 373 adolescents at IFLS-5 (2014) that folllowed at IFLS-3 (2000) and at IFLS-2 (1997). The effect of childhood undernutrition on the risk of pre-diabetes and diabetes in adolescents was analyzed using multinomial logistic regression. The results of this study showed that the prevalence of pre-diabetes was 12.6% and diabetes was 15.0%. The risk factor for pre-diabetes is frequent consumption of fast food (aOR=4.38). Meanwhile, recovering from stunting was a protective factor in adolescents (aOR=0.05). Risk factors for diabetes were stunting (aOR=2.71), deteriorated nutritional status during childhood (aOR=3.85), experienced wasting during childhood (aOR=3.55), and frequent fast food consumption (aOR=3.11). Meanwhile, vegetable consumption was a protective factor of diabetes (aOR=0.37). In conclusion, this study showed that childhood undernutrition on the risk of diabetes. Improvement point is through nutrition programs in childhood and adolescence.